'A philosopher's grammar': Henry Sweet's 'general', 'universal', and 'philosophical grammar'. (2nd January 2022) - Subbiondo, Joseph L.
ABSTRACT: Henry Sweet (1845–1912) defined a philosophical grammar (which he referred to as philosophical, general and universal grammar) as a grammar 'not concerned with the details of one special language or family of languages, but with the general principles that underlie the grammatical phenomena of all languages' (1892: 3). His philosophical grammar, compared to the comparative philological grammars that dominated the nineteenth century, was not only far more expansive and inclusive, but it also reflected Sweet's unique integration of practical and theoretical grammars. This paper focuses on Sweet's philosophical grammar from its introduction in 'Words, Logic, and Grammar' (1876) to its role in A New English Grammar (1892) and The History of Language (1900a).